Oral delivery of decanoic acid conjugated plant protein shell incorporating hybrid nanosystem leverage intestinal absorption of polyphenols. (February 2022) - Miao, Ruimin; Jin, Fanqi; Wang, Zhigao; Lu, Weijia; Liu, Junhong; Li, Xinyang; Zhang, Rui Xue
Abstract: Polyphenols are potent antioxidants, but their poor oral bioavailability owing to intrinsic insolubility and low permeability significantly hampers their effectiveness for clinical translation. Herein, upper intestinal absorptive polymer-lipid hybrid nanoparticles (PLN) was designed by exploiting the lipidic core for drug encapsulation and the decanoic acid conjugated rapeseed protein as the biopolymeric shell for gastrointestinal stability, retention and permeability. Polyphenol ellagic acid loaded core-shell PLN (EA-PLN(C/S)) was characterized of favorable physicochemical properties in simulated gastric- and intestinal fluids, including high drug loading capacity, slow drug release and prolonged stability. In Caco-2 monolayers, the cellular transport of EA-PLN(C/S) involved dual-paracellular and endocytosis pathways. Compared to drug in suspension or lipidic core nanoparticles, orally administered EA-PLN(C/S) was retained longer and more permeable via the duodenum and jejunum of upper intestine, resulting in up to 5.3-fold and 1.4-fold enhancement in the extent of drug absorption and colonic accumulation, respectively. In an acute colitis murine model, EA-PLN(C/S) at 6 mg/kg low dose markedly reduced colonic lipid peroxidation in contrast to no antioxidant effect in other EA formulations. This work suggests that integration of engineered plant protein biopolymer with lipid nanoparticles created unique oral drug delivery systems enabling intestinal site-specific absorption for effective antioxidant therapeutics. Graphical abstract: Image 1